Estymacja dopuszczalnych efektów stałych i losowych w modelach liniowych - Synówka-Bejenka, Ewa
The problem of admissibility of linear estimators of fixed and random effects in linear model in which the set of covariance matrices is finitely generated was considered. To give a characterization of admissible estimators this problem was reduced to linear estimation of the fixed effects only in model being correct extension of the original model. The explicit formulae for all admissible linear estimators in balanced models: nested classification, crossed classification and crossed classification with interaction were obtained. A necessary and sufficient conditions for linear estimators to be admissible in general linear model with two components were given also.
Keywords: model liniowy; estymacja liniowa; predykcja liniowa; estymacja dopuszczalna; estymator lokalnie optymalny